Telecommunications network modelling, planning and design - Evans, Sharon 1966- (Institution of Engineering and Technology, 2003)
This book addresses sophisticated modelling techniques from the perspective of the communications industry and covers some of the major issues facing telecommunications network engineers and managers today. Topics covered include network planning for transmission systems, modelling of SDH transport network structures and telecommunications network design and performance modelling, as well as network costs, ROI modelling and QoS in 3G networks.